The Crane Perspective. The Crisis of Female Identity in Hitchcock’s Psycho - Laura Antón (Feminismo/s, 2016)
Taking as a starting point reading built around this famous film of the modern horror film, this analysis suggests an overall reading of his discourse about the woman. Try to recover what we have become accustomed to forget, or at best, to score because it has been overshadowed by other issues. And is that beyond Norman and splitting monster mother-son, in the second part of the film another female character, the other sister Crane appears. What symbolizes this (double) perspective Crane? The main hypothesis management to answer this question is that this representative text of the discourse audiovisual crisis Hollywood, the film signifier of femininity undergoing a symbolic split proposed by Marion and Lila. Through this narrative strategy that has meant the question of identity, discourse of the film dramatizes the modern way, excessively, an identity crisis of women in a historical period, the beginning of the sixties, significant changes to the cultural role expected of women in American society.